Pengaruh Model Project Based Learning (PJBL) Terintegrasi Pembelajaran Mendalam terhadap kreativitas Siswa - Neriani; Hadi Purwanto (PT. Nawa Edukasi Nusantara, 2026)
This study aims to examine the impact of implementing the Project-Based Learning (PjBL) model combined with deep learning on student creativity through a literature review. The methodology employed is a literature review analyzing articles from national and international journals relevant to PjBL, deep learning, and student creativity. The findings indicate that PjBL fosters active, collaborative, and contextual learning experiences focused on problem-solving, thereby encouraging students to generate new ideas and creative works. Meanwhile, the integration of deep learning further strengthens this process by promoting meaningful conceptual understanding, reflective activities, and connections between knowledge and daily life. Overall, the implementation of PjBL integrated with deep learning positively influences student creativity, particularly regarding fluency of thought, flexibility, originality of ideas, idea development, and learning enthusiasm.